Negociaciones entre la cultura andina y la cultura urbana limeña en Madeinusa y La teta asustada de Claudia Llosa - Marie-Eve Monette (Nuevo mundo - Mundos Nuevos, 2013)
Madeinusa (2006) and The Milk of Sorrow (2009), the two first films of Peruvian director Claudia Llosa, present a renewed perspective of the Andean communities of Peru based on a dichotomy between continuity and change in their culture. Although it is certain that the two films depict some members of these communities as strong individuals who resist the influence of the urban culture of Lima, others also demonstrate that they constantly aspire to develop their own Andean identity, enriched by both Andean culture and the appropriation of the capital’s social characteristics. Madeinusa and Fausta, the protagonists of Madeinusa and The Milk of Sorrow, by confronting the vision of their communities and of the hegemony of Lima, are the individuals who aspire most strongly to balance this dichotomy.